The Necessity of Advancing Our Knowledge on Assistive Technologies to Better Support Students with Attention Deficit Hyperactivity Disorder - Mackenzie Genevieve; Ferrari Julia (Journal of ADHD And Care, 2017)
Individuals with ADHD may benefit from assistive technologies (ATs). ATs include FM systems, MontivAIDR, Time Aids, iSelfControl and Kurzweil. Eligibility for acquiring these ATs is discussed first. The importance of eligibility is highlighted because the review of the literature suggests that these ATs may promote academic success among students with ADHD. Unfortunately, most of the research on the efficacy of ATs is directed at learning disabilities. Consequently, a review of ATs that support students with learning disabilities is provided with the overarching goal to encourage researchers to determine how ATs that support students with learning disabilities may also support students with ADHD. Finally, we discuss the ways in which ATs can maintain their efficacy over time for students with ADHD through the implementation of a Response to Intervention (RTI) framework. Concluding remarks will follow.
Keywords: ADHD